Asuhan Keperawatan Pada Ny. U Dengan Post Operasi Sectio Caesarea Indikasi Partus Lama Di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Harfani Yulianti Aziz; Tati Karyawati; Siti Fatimah (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Childbirth is the process of opening and thinning the cervix and the fetus descending into the birth canal then ending with the expulsion of a baby that is term or almost term or can live outside the womb followed by expulsion of the placenta and fetal membranes from the mother's body through the birth canal or non-birth canal , with help or without help (own strength). Childbirth is considered normal if the process occurs at term (after 37 weeks) without complications (Prastiwi et al., 2020).